KAB Newsletter Issue 01 – March 2022 - Nowamani, Collins; Sempungu, Joseph Godfrey (Kabale University, 2022)
In this Issue: The Ministry of Water & Environment holds the Southwestern Uganda water day symposium at KAB The Chancellor, Prof. Mondo Kangonyera officiates at a book launch The Vice Chancellor’s tribute to the late Central Bank Governor, Prof. Emmanuel Tumusiime - Mutebile KAB hosts global scholars KABSOM trains health workers in selected districts of Kigezi Makerere University Research & Innovations fund explores a partnership with KAB Rotary donates cervical cancer screening & treatment equipment to selected districts of Kigezi KAB receives a grant from Canadian partners KAB to host Kiswahili international conference The French embassy in Kampala partners with KAB